ENNOBLEMENT OF THE ORTHODOX /GREEK CATHOLIC CLERGY IN PRZEMYŚL LAND (THE 16th – 18th CENTURIES): LEGAL CONFLICTS AND EVERYDAY REALITY - SMUTOK , Ihor; TUCHAPETS, Vasyl (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the study is to do a comprehensive research on a separate aspect of inter-estate relations in the Old Polish-Lithuanian Commonwealth, in particular, the ennoblement of priestly families and the mechanisms by which they achieved social success. The research methodology is based on the principles of historicism, scientificity, verification, as well as on the use of general scientific (analysis, synthesis, generalization) and special historical (prosopographic, historical and typological, historical and systemic) methods. Scientific Novelty. The study focuses on a previously unknown aspect of inter-estate relations in the Polish-Lithuanian Commonwealth, in particular the entry of the Orthodox and later Greek-Catholic clergy into the nobility (szlachta in Polish). The scope and mechanisms of this phenomenon have been elucidated through the prism of the legal field and everyday practice. Conclusions. The noble class of the Old Polish-Lithuanian Commonwealth, despite its apparent isolation, was constantly replenished with new families. Among them there were descendants of the Orthodox (Greek-Catholic) clergy. This phenomenon is observed in the territory of modern Western Ukraine (the Ruthenian Voivodeship). Within the boundaries of Przemyśl land, four dozen priestly families managed to improve their social status. All known cases of clergy ennoblement took place in the area of compact residence of the Ruthenian (Ukrainian) nobility (szlachta). After all, ennoblement was achieved not by legal instruments, but by close coexistence and kinship between the nobility and the local clergy. The life circumstances in which this latent ennoblement was carried out were different. However, certain trends and mechanisms of this process were common. Priests and their descendants, living in villages where the nobility lived compactly, acquired land ownership, became related to local families. Some of them changed their surnames to noble ones. Individual families lived in royal estates. They also achieved ennoblement through kinship with the nobility. However, the memory of their unprivileged origin persisted and their noble status was permanently questioned by the local noble community. Keywords: nobility (szlachta) in Przemyśl land, Orthodox clergy, Greek Catholic clergy, Przemyśl diocese.